Role of trade unions in the event of employment disputes that have an impact on termination of employment (layoffs) - Enggartiasti Sherly Anggraini; Siti Hajati Hoesin (The International Journal of Politics and Sociology Research, 2023)
In every company, always strives to create a cooperative and comfortable work environment for every employee. However, it is not uncommon for disputes or conflicts to occur in a company due to differences of opinion or matters that are not in accordance with the regulations in force in Indonesia. When a dispute occurs, sometimes employees need representatives to convey their aspirations or act on behalf of employees. With the existence of a workers' union in a company, it is intended for all aspirations will be better conveyed and create a harmonious relationship between the Company and employees. Many companies currently have labor unions to improve the welfare of workers, including when there is a dispute over work relations whether it ends in termination of employment or not. By using normative research techniques, this paper is intended to discuss the role of trade unions, especially those that have an impact on termination of employment.